Commuter Boarding Management Practices and its Effects on Passenger Experience at Cebu South Bus Terminal, Philippines - Keers E. Adolfo; Oudy Francis A. Acedo; Mova M. Alicaway; Gwendolyn G. Anoya; Kristine A. Aratia; Nesta Rudy Marcus P. Flores; Lalaine O. Narsico; Peter G. Narsico (Future Science / FSH-PH Publications, 2026)
Effective boarding is necessary for the maintenance of order and promoting commuter satisfaction in high-traffic terminals. Long queues and delays remain an ongoing problem at Cebu South Bus Terminal. The effectiveness of boarding management practices and their impact on commuter satisfaction was investigated in this paper. We employed descriptive-correlational design with 511 commuters (18–50 years old) who use the terminal regularly. Data was collected using a structured survey using a five-point Likert scale to evaluate the adoption of boarding practices and passenger satisfaction. All data were summarised in weighted means, and simple linear regression was used to check the relationships between variables. (mean = 3.37) Boarding management practices were rated as Occasionally Observed (with strengths in fairness, announcements, and lane discipline, but weakness in staff availability and boarding time). Passenger experience was equally Occasionally Observed (mean = 3.35) with safety and willingness to recommend rated higher than waiting time and comfort. Results from regression analysis (R = 0.871; R² = 0.759; p < 0.001) confirmed a strong positive relationship between boarding practices and passenger satisfaction and significant effect was also confirmed by coefficient analysis (β = 0.895). Boarding management has a strong prediction of passenger satisfaction: 76% of the variance in the passenger satisfaction. Operational improvements should emphasize staffing, communication, lane discipline, and fairness (supported by standardizing the operations through standardization, training, and real-time monitoring) based on Standard Operating Procedures. Further investigations might focus on technological assistance methods, passenger segmentation, and longitudinal evaluations to assess the effects of interventions.